Practitioners' reasons for remaining in physical exercise programs offered by the Social Service of Commerce − Brazil - A. Palma; W. Monteiro; N.L. Silva; M.S. Castro; H.G. Resende (Desafio Singular, 2010)
One of the concerns in the studies of adhesion lies in the investigation of the motives that justify continuation in physical exercise programs. The goal of this study was to identify motives influencing the continuation of adolescents, adults and the elderly in physical education programs offered by the Centers of Activity of Serviço Social do Comércio do Distrito Federal do Brasil. A representative and random sample of 986 individuals (between 15 and 89 years of age) answered a data collection instrument designed to investigate socio-demographic aspects and motives for permanence in the aforementioned program. Results showed personal wellbeing (91.9%) as the major reason for keeping up on practicing followed by prevention of illnesses (82.8%), physical conditioning (80.7%), empathy with the teacher (79.2%), program methodology (75.2%), and entertainment (73.9%). While medical exercise prescription highly influences people's entrance in these programs, it does not explain people's continuance.